201k views
3 votes
Solve the system using the ‘substitution’ technique:

-2x + 3y = 1.2
-3x - 6y = 1.8
Please show your work.

User Sock
by
6.1k points

1 Answer

5 votes

Answer:

The answer to your question is x = -0.6, y = 0 or (-0.6, 0)

Explanation:

Equations

-2x + 3y = 1.2 ------------------ (I)

-3x - 6y = 1.8 ------------------ (II)

Solve equation I for y

3y = 2x + 1.2

y = 2/3x + 1.2/3

Substitute in equation II

-3x - 6(2/3x + 1.2/3) = 1.8

Simplification

-3x - 4x - 2.4 = 1.8

Solve for x

-7x = 1.8 + 2.4

-7x = 4.2

x = 4.2/-7

x = - 0.6

Find the value of y

y = 2/3 (-0.6) + 1.2/3

y = -0.4 + 0.4

y = 0

User Blondelg
by
6.3k points